Religious conflicts in Nyíregyháza - the difficulties of an eighteenth century Slovak settlement - Kupa, László (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2008)
The resettlement of wide areas of Hungary, and especially those in peripheral areas, in the years following the end of the Turkish occupation is a large and complex subject. This particular study introduces the 18th century settlement of Nyíregyháza, a long and painful process in which it was the religious identity of the Slovak Lutheran settlers which was the dominant issue rather than their ethnic origin. We deal in some detail with those conflicts which developed between the settlersć landlord (Count Ferenc Károlyi) and the bishop of Eger (Count Ferenc Barkóczy) over the settlement itself. These conflicts were closely related to the re-catholicisation processin Hungary which played an important role even in the mid-18th century.
Keywords: Hungary; Madžarska; verski konflikti; Slovaki; Slovakia; poselitev; verske manjšine; 18.st.